Optimization of imaging protocols for myocardial blood flow (MBF) quantification with 18F-flurpiridaz PET. (October 2017) - Wiyaporn, Kanyalak; Tocharoenchai, Chiraporn; Pusuwan, Pawana; Higuchi, Takahiro; Fung, George S.K.; Feng, Tao; Park, Min Jae; Tsui, Benjamin M.W.
Highlights: We optimized protocols for lowest myocardial blood flow (MBF) quantification error. MBF error was decreased with increasing update numbers of OS-EM algorithm. Too fast or too slow infusion with short sampling times provided higher MBF error. Our study demonstrate the use of a realistic simulation study based on extrapolated animal data to optimize the dynamic data acquisition protocol and image reconstruction for 18 F-flurpiridaz PET imaging in human while clinical data from a Phase III study are not available yet. Abstract: The new PET tracer, 18 F-flurpiridaz, with high myocardial extraction allows quantitative myocardial blood flow (MBF) estimation from dynamic PET data and tracer kinetic modeling. The goal of this study is to determine the optimal imaging protocols and parameters using a realistic simulation study. The time activity curves (TACs) of different tissue organs from a 30-s infusion time (IT) of 18 F-flurpiridaz in a dynamic PET study were extracted from a previous study. The TACs at different time points were incorporated in a series of realistic 3D XCAT phantoms from which the parameters of a 2-compartment model and the 'true' MBF of 18 F-flurpiridaz were determined. The compartmental model was used to generate TACs from 7 additional ITs. PET projection data from the XCAT phantoms were generated using Monte Carlo simulation. They were reconstructed using an OS-EM reconstruction algorithm with different update number (N) to obtain dynamic PET images. The blood and myocardial TACs were derived from the dynamic images from which the MBF and %MBF error was estimated. The %MBF error decreases with increasing N of the OS-EM and levels off after ∼42. The 30-s IT gave the smallest %MBF error that decreases from ∼0.57% to ∼19.40%. The MBF for 2-min, 4-min, 8-min and 16-min IT were statistically significant different from the MBF for 30-s IT (P < 0.05). Too fast or too slow infusion time gave higher %MBF error. The optimal imaging protocol in dynamic 18 F-flurpiridaz PET for accurate quantitative MBF estimation was 30-s IT and N of ∼42 for the OS-EM.